Depiction of the Tirthankara Parshvanath standing on a multi-headed naga (serpant) - Temples of India Project (Jio Institute, 2024)
This painting in the inner/upper circle in the ceiling of the mandapa (pillared hall) depicts the 23rd Jain Tirthankara, Parshvanath, standing on a multi-headed naga (serpant), with the hood crown positioned above the head of the lord. A naga couple in anthropomorphic form stands flanking the Tirthankara and bows down to him. Parshvanath wears a crown and is adorned with jewellery. There are two gandharvas (celestial beings) in the sky above him. The inscription reads, ‘Parasnath Shvami.’